STRATEGI PENGEMBANGAN AGROWISATA DENGAN MENGGUNAKAN BLUE OCEAN STRATEGY MODEL. STUDI KASUS PERKEBUNAN KOPI GREEN SAGO KABUPATEN 50 KOTA. - Fauzan, Rusydi; Rahmadani, Suci (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2018)
This study aims to increase the level of visits to Green Sago Coffee Agro Tourism using the Blue Ocean Strategy approach. This type of research is a qualitative descriptive study. Data collection techniques are done by observation and interviews. Research using analytical tools includes: a strategy canvas, a four-step framework, and complementary qualities. The results of the study provide recommendations for the three main strategies of Blue Ocean Strategy: 1) a focused strategy that offers experience to become farmers, ranchers, fish farmers, medicine mixers, tree conceptualists and agribusiness entrepreneurs, 2) a divergence strategy that offers activities: management of agricultural land, animal care, fish cultivation, tree care, drug manufacturing, and garden management, and 3) a motto strategy, namely: providing